The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2106/jbjs.18.00997
|View full text |Cite
|
Sign up to set email alerts
|

Implant Fracture Analysis of the TFNA Proximal Femoral Nail

Abstract: Background: Mechanical failure of intramedullary nails is rare. This investigation was prompted by a series of cases of observed breakage of the recently introduced TFNA Proximal Femoral Nailing System (TFN [Trochanteric Fixation Nail]-Advanced; DePuy Synthes) in our region. Laboratory analysis and case data are presented, in contribution to post-market surveillance. Methods: Medical and imaging records from the 3 public tertiary orthopaedic trauma hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 8 publications
2
55
2
Order By: Relevance
“…Meanwhile, Lambers et al all six cases showed successful bone union during followup, and no implant fracture occurred during or after the six-month radiological assessment. 7) In seven cases of long nail use, there was no iatrogenic fracture or perforation of the distal anterior cortex at the distal femur, which results from a mismatch between femur and nail. The ROC of the newly designed TFNA is 1.0 m, and the curvature is increased compared to the conventional TFN, which has a ROC with a radius of 1.5 m. 4,5) Asian patients usually have more femoral bowing than do Western patients.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Meanwhile, Lambers et al all six cases showed successful bone union during followup, and no implant fracture occurred during or after the six-month radiological assessment. 7) In seven cases of long nail use, there was no iatrogenic fracture or perforation of the distal anterior cortex at the distal femur, which results from a mismatch between femur and nail. The ROC of the newly designed TFNA is 1.0 m, and the curvature is increased compared to the conventional TFN, which has a ROC with a radius of 1.5 m. 4,5) Asian patients usually have more femoral bowing than do Western patients.…”
Section: Discussionmentioning
confidence: 89%
“…1). [4][5][6] Despite the many advantages of the new design characteristics of TFNA, Lamber et al 7) recently published a worrisome report of 16 cases of early implant breakage in the treatment of hip fracture patients. According to the data, implant failure mostly occurred in AO/OTA 31A3 fractures (reverse oblique type), and almost all implant fractures occurred at the proximal aperture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggested cautious surveillance of patients with unstable hip fracture who were treated with a TFNA implant. [20] They did not evaluate the CCD angle of the broken nails.…”
Section: Resultsmentioning
confidence: 99%
“…Lamber et al found that TFNA nail breakage was seen mostly in unstable fracture patterns in their case series [ 15 ]. They also hypothesized that the reduced cross-sectional area of the TFNA at the level of the proximal screw aperture, changes in the alloy compared with its predecessors may be of importance in breakage of the TFNA at that site [ 15 ]. In our patient, since there was a cut-out of the helical blade from the femoral head, it was not possible to salvage the femoral head; therefore, we opted for bipolar hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 99%